A novel decision tree searcidng algorithm for high speed online traffic classification - Izzeldin Ibrahim, Mohamed Abdelaziz
Research methodology represents the basis behind a research study as it dictates the selection of methods for data collection and analysis, as well as the perspective applied for analysis interpretation. As such, this section describes and discusses the research methodology employed in both designing and evaluating a novel decision tree searching algorithm for high speed online traffic classification